The Effect of Tax Incentives, Financial Distress and Leverage on Accounting Conservatism - Darma, Sapta Setia (EAJ (Economic and Accounting Journal), 2023)
This study aims to provide empirical evidence of the effects of Tax Incentives, Financial Distress, and Leverage on Accounting Conservatism. This type of research is quantitative. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017-2021. The sample used in this study took 175 data from 35 manufacturing companies listed on the Indonesia Stock Exchange. The data analysis technique in this study used the classical assumption test, multiple linear regression analysis, and hypothesis testing with the help of the Statistical Package For Social Sciences (SPSS) version 22 program. Based on the test result,s it was found that partially Financial Distress and leverage did not significantly affect Accounting Conservatism. In contrast, tax incentives had a significant influence on Accounting Conservatism. Simultaneously Tax Incentives, Financial Distress and Leverage affect Accounting Conservatism. The research findings provide practitioners, internal (managers and business owners, both local and multinational organizations), and external (policymakers, foreign investors) new insights into applying conservative accounting policies, which are influenced by various factors.